COVI-Prim Longitudinal Survey: Experiences of Primary Care Physicians During the Early Phase of the COVID-19 Pandemic - Schaffler-Schaden, Dagmar; Mergenthal, Karola; Avian, Alexander; Huter, Sebastian; Spary-Kainz, Ulrike; Bachler, Herbert; Flamm, Maria; Siebenhofer, Andrea (Frontiers in Medicine, 2022)
Background General practitioners (GPs) are the mainstay of primary care and play a critical role in pandemics. During the first wave of the COVID-19 pandemic, this international study aimed to explore changes in the workload of general practitioners, as well as their interactions with patients and colleagues, and their self-confidence and concerns. Methods An online survey was conducted among GPs in Austria and Germany. Participants were asked to answer a basic questionnaire and participate in a subsequent longitudinal survey containing closed and open-ended items. All data were pseudonymized. Results Overall, 723 general practitioners from Austria and Germany took part in the longitudinal survey over a period of 12 weeks (April 3–July 2, 2020). The majority of GPs had less direct contact with patients at the beginning of the survey (96 vs. 49% at the end of the study period). At first, doctors were mainly concerned with pandemic-related issues and had to care for the patients of GP colleagues that were in quarantine, which meant they had less time for routine work such as screenings and treating chronic diseases. Over the survey period, GPs' self-confidence increased and their concerns about income loss decreased. Conclusions Following a difficult initial phase when protective equipment and information were lacking, physicians in primary care adapted quickly to new situations. Experience with telemedicine should help them face future challenges and may help prevent a decline in the delivery of routine health care and care for chronically ill patients. Registration Trial registration at the German Clinical Trials Register: DRKS00021231.